Development and pharmacokinetic assessment of a fully canine anti-PD-1 monoclonal antibody for comparative translational research in dogs with spontaneous tumors - Sho Yoshimoto; Nicholas Chester; Ailian Xiong; Enrico Radaelli; Hong Wang; Marc Brillantes; Gayathri Gulendran; Patrick Glassman; Don L. Siegel; Nicola J. Mason (Taylor & Francis Group, 2023)
ABSTRACTPD-1 checkpoint inhibitors have revolutionized the treatment of patients with different cancer histologies including melanoma, renal cell carcinoma, and non-small cell lung carcinoma. However, only a subset of patients show a dramatic clinical response to treatment. Despite intense biomarker discovery efforts, no single robust, prognostic correlation has emerged as a valid outcome predictor. Immune competent, pet dogs develop spontaneous tumors that share similar features to human cancers including chromosome aberrations, molecular subtypes, immune signatures, tumor heterogeneity, metastatic behavior, and chemotherapeutic response. As such, they represent a valuable parallel patient population in which to investigate predictive biomarkers of checkpoint inhibition. However, the lack of a validated, non-immunogenic, canine anti-PD-1 antibody for pre-clinical use hinders this comparative approach and prevents potential clinical benefits of PD-1 blockade being realized in the veterinary clinic. To address this, fully canine single-chain variable fragments (scFvs) that bind canine (c)PD-1 were isolated from a comprehensive canine scFv phage display library. Lead candidates were identified that bound with high affinity to cPD-1 and inhibited its interaction with canine PD-L1 (cPD-L1). The lead scFv candidate re-formatted into a fully canine IgGD reversed the inhibitory effects of cPD-1:cPD-L1 interaction on canine chimeric antigen receptor (CAR) T cell function. In vivo administration showed no toxicity and revealed favorable pharmacokinetics for a reasonable dosing schedule. These results pave the way for clinical trials with anti-cPD-1 in canine cancer patients to investigate predictive biomarkers and combination regimens to inform human clinical trials and bring a promising checkpoint inhibitor into the veterinary armamentarium.